PENGENALAN MANAJEMEN BISNIS SYARIAH MELALUI PELATIHAN KEWIRAUSAHAAN PADA KELOMPOK TANI DI KAMPUNG CENGAL, DESA KARACAK, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Desti Amanda Riyani; Ujang Buchori Muslim; Hasbi Ash Shiddieqy (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2021)
Abstract This community service activity was carried out on Tuesday, September 22, 2020 at kp. Cengal RT 01 RW 05 Karacak Village, Leuwiliang District, Bogor Regency. the purpose of this activity is to provide training to farmer groups and the kp.cengal community to process agricultural products into other products so that they can increase added value and provide information on how to develop businesses by marketing good products, namely through digital marketing. The activity method in its implementation uses various methods such as presentations, discussions, questions and answers, as well as providing digital marketing training for farmer groups in kp. block out. The results of the activity are speakers, namely lecturers who have been prepared by the implementation committee, this entrepreneurship counseling provides training on motivation in entrepreneurship, procedures for licensing MUI halal certification, business planning to packaging and labeling, along with product marketing strategies through digital marketing. for farmer groups so that the practice given in this Community Service activity is a simulation of building a new business and planning its marketing. This activity was very well received, as seen from the enthusiasm of the community in participating in the activities and discussions. Keywords: entrepreneurship training, farmer groups, digital marketing